Analisis Literatur Tentang Efektivitas Sistem Bagi Hasil Dalam Pembiayaan Mudharabah Pada Perbankan Syariah - Radiansyah, M; Munawaroh, Munawaroh (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This study aims to analyze the implementation of mudharabah contracts in Islamic banking in Indonesia and their impact on economic growth, particularly in the Micro, Small, and Medium Enterprises (MSMEs) sector. Utilizing qualitative research methods with a literature review approach, this study explores various literature and previous research findings discussing the mechanisms, challenges, and opportunities encountered in mudharabah financing. The results indicate that mudharabah contracts can not only enhance customer motivation but also provide a fairer financing alternative compared to conventional interest-based systems.